A technique for choosing a way of fixing for hip joint endoprosthesis components in patients with rheumatoid arthritis - Gerasimenko, Sergey; Poluliakh, Mykhaylo; Tymochook, Victor; Gerasimenko, Andrey; Belaya, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Results of treatment of 85 patients with rheumatoid arthritis, who underwent 118 operations of total hip joint arthroplasty, were retrospectively analysed. On the basis of a clinical-radiological investigation and questioning of patients, results of supersonic osteodensitometry, radiodensitometry, cultural-immunological studies of osteogenic activity of stromal stem cells of bone marrow in different areas of the hip joint plus a statistical processing of the obtained data, a technique was developed for point assessment of the state of the pelvic bone tissue in the acetabular region and of the femur in the intertrochanteric region.